Role and Strategy of Hotel Public Relations in Returning Guests After Selat Sunda Tsunami - Widya Nur Bhakti Pertiwi; Diqbal Satyanegara; Asmi Ayuning Hidayah (JURNAL SOSIAL HUMANIORA (JSH), 2020)
The purpose of this research is to figure out the role of public relations, as well as the strategy of public relations in the effort to improve the hotel occupancy rate in Anyer, Serang, Banten after the Selat Sunda tsunami. The methodology used in this study is a qualitative descriptive approach, with with in-depth interviews to collect data. This method of data collection is commenced by interviews with hotel managers in Anyer. The samples of this research are five hotels in Anyer Serang, Banten, to represent their respective classes: five-star hotels, four-stars, three-star, and budget hotels. The results of this study show that the PR of the hotels in Anyer have done their role well, but they have not been able to increase the maximum the number of room occupancy of the hotels in Anyer, Serang, Banten.